Adult mortality of diseases and injuries attributable to selected metabolic, lifestyle, environmental, and infectious risk factors in Taiwan: a comparative risk assessment - Wei-Cheng Lo; Chu-Chang Ku; Shu-Ti Chiou; Chang-Chuan Chan; Chi‐Ling Chen; Mei-Shu Lai; Hsien-Ho Lin (BMC, 2017)
Abstract Background To facilitate priority-setting in health policymaking, we compiled the best available information to estimate the adult mortality (>30 years) burden attributable to 13 metabolic, lifestyle, infectious, and environmental risk factors in Taiwan. Methods We obtained data on risk factor exposure from nationally representative health surveys, cause-specific mortality from the National Death Registry, and relative risks from epidemiological studies and meta-analyses. We applied the comparative risk assessment framework to estimate mortality burden attributable to individual risk factors or risk factor clusters. Results In 2009, high blood glucose accounted for 14,900 deaths (95% UI: 11,850-17,960), or 10.4% of all deaths in that year. It was followed by tobacco smoking (13,340 deaths, 95% UI: 10,330-16,450), high blood pressure (11,190 deaths, 95% UI: 8,190-14,190), ambient particulate matter pollution (8,600 deaths, 95% UI: 7,370-9,840), and dietary risks (high sodium intake and low intake of fruits and vegetables, 7,890 deaths, 95% UI: 5,970-9,810). Overweight-obesity and physical inactivity accounted for 7,620 deaths (95% UI: 6,040-9,190), and 7,400 deaths (95% UI: 6,670-8,130), respectively. The cardiometabolic risk factors of high blood pressure, high blood glucose, high cholesterol, and overweight-obesity jointly accounted for 12,120 deaths (95% UI: 11,220-13,020) from cardiovascular diseases. For domestic risk factors, infections from hepatitis B virus (HBV) and hepatitis C virus (HCV) were responsible for 6,300 deaths (95% UI: 5,610-6,980) and 3,170 deaths (95% UI: 1,860-4,490), respectively, and betel nut use was associated with 1,780 deaths from oral, laryngeal, and esophageal cancer (95% UI: 1,190-2,360). The leading risk factors for years of life lost were similar, but the impact of tobacco smoking and alcohol use became larger because the attributable deaths from these risk factors occurred among young adults aged less than 60 years. Conclusions High blood glucose, tobacco smoking, and high blood pressure are the major risk factors for deaths from diseases and injuries among Taiwanese adults. A large number of years of life would be gained if the 13 modifiable risk factors could be removed or reduced to the optimal level.